COHESION AND SOCIAL DISTANCE: THE COMMENSAL CONSUMPTION OF BOVIDS DURING FUNERARY RITUALS OF ARGARIC SOCIETIES - Aranda Jiménez, Gonzalo (Cuadernos de Prehistoria y Arqueología de la Universidad de Granada, 2008)
The social relevance attained by different forms of food consumption, especially those related to meat eating, will be analysed. The ritualisation of specific practices of consumption has traditionally been the perfect way to naturalize differential access to goods of production.In this context the slaughter and consumption of meat in Argaric funerary rituals could beunderstood as a symbolic expression that reproduces and legitimizes asymmetrical social relationships. At the same time, these rituals suppose the creation of cohesion and solidarity links across the different social groups. Therefore, rituals of commensality are one of the most important ways in which power in argaric societies is based on.